The Interactions of Plasminogen with Model Surfaces and Derivatized Polyurethanes - Woodhouse, Ann Kimberly (My University, 1992)
The major complication limiting the usefulness of biomaterials in blood contracting situations is the activation of the coagulation pathways resulting in platelet activation and thromous formation at the surface. These events are initiated by the surface phenomena. The initial interaction is believed to be the adsorption of proteins onto the artificial surface followed by stimulation of cells and their subsequent adherence to the protein layer. The research presented in this thesis take the approach of making the surface typically interactive to achieve biocompatibility, and focuses on plasminogen, a plasma protein not previously studied in detail relative to blood interactions with artificial surfaces. The underlying working hypothesis of this research is that a potentially fibrinolytic, i.e. clot-lysing, surface may be formed via the specific and selective adsorption of plasminogen following blood contact.
Our approach was to create materials that would selectively adsorb plasminogen from blood by incorporating lysine residues (known to bind plasminogen) into the surface. Several different materials have been developed to facilitate this investigation: polyurethanes substituted with lysine derived from sulphonated precursors, classical polyurethanes, and model silica glass materials fictionalized with sulphonic acid groups and subsequently derivatized with lysine.
The model surfaces (silica glass, silylated sulphonated silica glass, and lysinated silica glass) were used to develop a method for the lysine derivatization of materials which results in incorporation of lysine at the surface with a free ε-amine group. Chemical and physical characterization of the surfaces utilizing ninhydrin reagent, contact angle and X-ray photoelectron spectroscopy were done and molecular modeling of silylated glass surface was undertaken. The data obtained indicate both qualitatively and quantitatively that the silylation and lysine fictionalization methods were successful.
Protein adsorption from buffer and from citrated human plasma was investigated on all materials. Generally, the plasminogen adsorption from buffer was Langmuirian. Surface concentrations corresponding to monolayer protein adsorption were observed at the isotherm plateaus. The sulphonated and lysine derivatized materials showed higher adsorption capacities relative to other surfaces. Adsorption studies on the model materials from pure buffer, included both adsorption and the desorption experiments in the presence of competing species, and suggest that the binding mechanism of plasminogen is different on each of the surfaces. It seems likely that the lysine binding sites are involved at least to some extent in the adsorption of plasminogen to lysinated materials.
The adsorption studies of fibrinogen and plasminogen from plasma suggest that plasminogen may be a possible contributor to the fibrinogen Vroman effect. In addition these studies provide further data in support of the contention that sulphonate groups have a strong influence on the adsorption of proteins in general. The plasma studies also show that the ratio of plasminogen to fibrinogen is greater on the lysinated than on the control on the sulphonated material, again indicating a specific influence of the lysine residues.
Data on the enzymatic activity of plasminogen adsorbed on the lysinated silica glass and its sulphonated precursor are reported. These studies provide information on the effect of lysine derivatization on the very important question of plasmin activity of adsorbed plasminogen. It was found that the plasminogen is no "plasmin-like" when adsorbed to any of the surfaces studied in this system. However in the presence of plasminogen activator there is a highly significant difference in the enzymatic activity of plasminogen adsorbed to the lysinated materials and to its sulphonated precursor. The lysinated material shows two-four times the plasmin activity on a mole basis compared to the sulphonated material. The implications of these findings for the development of fibrinolytic surfaces are discussed.
Preliminary investigations into polyurethanes derivatized using methods developed with the model materials are also reported.
Keywords: Chemical Engineering; Chemical Engineering